Influence of shod/unshod condition and running speed on foot-strike patterns, inversion/eversion, and vertical foot rotation in endurance runners - Muñoz-Jimenez, M.; Latorre-Román, P. A.; Soto-Hermoso, V. M.; Garcia-Pinillos, F. (Journal of Sports Sciences, 2015)
The aim of this study was to determine the influence of barefoot running on foot-strike patterns, eversion-inversion, running speed and vertical foot rotation in endurance runners. Eighty healthy recreational runners (age = 34.11 ± 12.95 years old, body mass index = 22.56 ± 2.65 kg · m-2) performed trials in shod/unshod running conditions on a treadmill at comfortable and competitive self-selected speeds. Data were collected by systematic observation of lateral and back recordings at 240 Hz. McNemar`s test indicated significant differences between shod/unshod conditions and foot strike at comfortable and competitive speeds (P < 0.001). Speed was related to vertical foot rotation type for shod (P < 0.01) and unshod conditions (P < 0.05). Significant differences were found between shod/unshod conditions in foot rotation at comfortable running speeds (P < 0.001) and competitive running speeds (P < 0.01). No significant difference was found in inversion or eversion (P = 0.05). In conclusion, the results suggest that running kinematics, in terms of foot-strike patterns and vertical foot rotation, differ between shod/unshod conditions, while the inversion or eversion degree remains unchanged.